Positional Stability and Change in Vocabulary and Literacy Between Ages 4 and 11 - Taylor, C. L.; Lawrence, D; Taylor, C; Zubrick, S; Mitrou, F; Christensen, D; Zubrick, S. R. (My University, 2012)
Following a group of children across four waves of the Longitudinal Study of Australian Children we have assessed their receptive vocabulary at ages 4-5, 6-7 and 8-9, using the Peabody Picture Vocabulary Test and their onward literacy at ages 10-11 using the teacher-rated Academic Rating Scale. This allows us to assess positional stability and change, that is the extent to which children with lesser receptive vocabulary at Wave 1 remain in the lower performing group across time. We also discuss the risks associated with persistently low vocabulary and literacy, and predictors of group membership, including child factors such as child sex and birthweight and family factors such as family income and parental education.
Keywords: Families -- Socio-economic status; Child Development -- Speech and Language; Childhood and child development; Families and relationships; Families; Child Development; Socio-economic status; Speech and Language; Families and relationships; Childhood and child development